Global gene analysis of late secretory phase, eutopic endometrium does not provide the basis for a minimally invasive test of endometriosis - J. R. A. Sherwin; Andrew Sharkey; Attila Mihalyi; Péter Simsa; Rob D. Catalano; Thomas D’Hooghe (2008)
Endometriosis occurs in 10% of women and is currently diagnosed by invasive laparoscopic testing. We tested the hypothesis that endometrial gene expression in late secretory phase endometrium differs between patients with and without endometriosis.Ten patients with laparoscopically proven endometriosis (minimal/mild n = 5 and moderate/severe n = 5) and six controls, underwent endometrial biopsy in the late secretory phase (Day 23 onwards). Microarray interrogation of eutopic endometrial gene expression was performed.Microarray data were obtained for all control samples and eight samples from the endometriosis patients (n = 4 minimal/mild, n = 4 moderate/severe disease). Eight genes were identified as up-regulated and one gene was down-regulated in all endometriotic samples (more than 1.75-fold, P < 0.01). Real-time PCR analysis of protocadherin-17 (PCDH17), protein tyrosine phosphatase, receptor type, R (PTPRR) and interleukin-6 signal transducer (IL6ST) expression validated the microarray findings.Expression of very few transcripts differs, in late secretory eutopic endometrium, between controls and patients with endometriosis. The median fold changes of these genes are small. No transcripts were identified that could discriminate between minimal/mild and moderate/severe endometriosis. Therefore, interrogation of the late secretory endometrial transcriptome is not likely to form the basis of a minimally invasive diagnostic test for endometriosis.